Hepatic resection for post‐operative solitary liver metastasis from oesophageal squamous cell carcinoma. Issue 4 (20th October 2016) - Liu, Jingeng; Wei, Zhiru; Wang, Yuebin; Xia, Zongjiang; Zhao, Gaofeng
Abstract : Background: Liver metastasis is common in patients with oesophageal cancer. The effect of operative intervention for post‐operative solitary liver metastasis from oesophageal squamous cell carcinoma (ESCC) has not previously been examined. This research was to compare the effect of surgery and non‐surgical therapy in patients with post‐operative solitary liver metastasis from ESCC. Methods: We retrospectively analysed the clinical data of 69 consecutive patients with solitary hepatic metastasis who had undergone oesophagectomy for ESCC and were subsequently referred to the First Affiliated Hospital of Zhengzhou University from January 2005 to December 2013. The survival rates of the surgical and non‐surgical groups were compared. Results: There were 26 patients in the surgical group and 43 patients in the non‐surgical group. There was no operative death in the surgical group. Post‐operative complications were observed in six patients, and all of these patients recovered after additional treatments. Patients in the surgical group had 1‐ and 2‐year cumulative survival rates of 50.8 and 21.2%, respectively, which were significantly higher than the 31.0 and 7.1% survival rates of patients in the non‐surgical group ( P  < 0.05). In each group, the patients with a disease‐free interval (DFI) lasting >12 months had a better survival rate than those with a DFI lasting ≤12 months (all P  < 0.05). Conclusions: Operative intervention is a better treatment choice for patients with post‐operative solitary liver metastasis from ESCC, especially for patients with a DFI lasting >12 months. Patients selected for hepatic resection should be considered on an individual basis through a multidisciplinary team of specialists.